African–American Women's Tobacco and Marijuana Use: The Effects of Social Context and Substance Use Perceptions. (12th May 2019) - Oser, Carrie B.; Harp, Kathi; Pullen, Erin; Bunting, Amanda M.; Stevens-Watkins, Danelle; Staton, Michele
Abstract: Background : Despite the status of tobacco and marijuana as two of the most commonly used substances in the U.S., both have detrimental health and social consequences for disfranchized African–Americans. Substance use may be shaped by social contextual influences from families and peers in African–American communities, and little research has examined perceptions of wrongfulness, harms, and dangers associated with daily tobacco and marijuana use among African–American women. Objectives : This study explores the effects of African–American women's social context and substance use perceptions (wrongfulness/harmfulness/dangerousness) on daily tobacco and marijuana use. Methods : Survey data was collected in-person from 521 African–American women. Multivariate logistic models identified the significant correlates of women's daily use of tobacco and marijuana in the past six months. Results : 52.59% of participants reported daily tobacco use and 10.56% used marijuana daily. Multivariate models indicated that women were more likely to be daily tobacco users if they had a family member with a substance use problem or perceived tobacco use to be wrong, harmful, or more dangerous than marijuana. In the models with marijuana as the dependent variable, women who lived with a person who used drugs were more likely to use marijuana daily. Perceiving marijuana use as wrong or harmful to one's health was protective against daily marijuana use. Conclusions : Findings stress the need for prevention and intervention efforts for African–American women that highlight social context influences and promote greater awareness of the health risks associated with daily tobacco and marijuana use.